2019
DOI: 10.3390/urbansci3010012
|View full text |Cite
|
Sign up to set email alerts
|

Using Building Floor Space for Station Area Population and Employment Estimation

Abstract: Analyzing population and employment sizes at the local finer geographic scale of transit station areas offers valuable insights for cities in terms of developing better decision-making skills to support transit-oriented development. Commonly, the station area population and employment have been derived from census tract or even block data. Unfortunately, such detailed census data are hardly available and difficult to access in cities of developing countries. To address this problem, this paper explores an alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In terms of Environment Sustainability, Transportation emerged with the highest weight (0.65), followed by Resource Use (0.23), and Development Form (0.12) as shown in Table 6. Given the pivotal role of transportation in driving developmental growth, its impact on environment sustainability is significant (Teh et al, 2019). A clear cause-and-effect example lies in the construction of roads to accommodate development, often at the expanse of depleting existing natural resources.…”
Section: Sustainability Dimension (Level 1)mentioning
confidence: 99%
“…In terms of Environment Sustainability, Transportation emerged with the highest weight (0.65), followed by Resource Use (0.23), and Development Form (0.12) as shown in Table 6. Given the pivotal role of transportation in driving developmental growth, its impact on environment sustainability is significant (Teh et al, 2019). A clear cause-and-effect example lies in the construction of roads to accommodate development, often at the expanse of depleting existing natural resources.…”
Section: Sustainability Dimension (Level 1)mentioning
confidence: 99%
“…Geospatial real estate and housing stock data has been included in the analysis, since it has repeatedly proven to be significant in previous population estimation approaches [ 6 , 15 ], and has been extensively linked to demography in other studies [ 49 51 ]. Examples of housing predictors that have been used are the number of buildings, their footprint area, floor area, and volume [ 20 , 47 , 52 , 53 ]. Nowadays, real estate datasets are available from commercial websites or the government, and may support population estimation methods significantly [ 15 , 28 , 54 ].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Current studies on the influence factors of public transportation ridership have varied from built environment [1][2][3][4][5] , socioeconomics [6] , transportation modes [7] and policy [8] . Regarding the built environment, Kuby [1] et al analyzed ridership data for 268 light-rail stations in nine US cities, revealing the importance of land use, employment, and rental rate factor.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the built environment, Kuby [1] et al analyzed ridership data for 268 light-rail stations in nine US cities, revealing the importance of land use, employment, and rental rate factor. Teh [2] et al found that building floor space is useful for estimating station ridership. Zhao [3] et al studied the correlation between land use and the construction of metro station in Beijing, while Jun [4] et al found that land use diversity positively affects metro station ridership in Seoul.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation